2019
DOI: 10.1021/acs.jpcb.9b03091
|View full text |Cite
|
Sign up to set email alerts
|

Toward Rational Design of Selective Molecularly Imprinted Polymers (MIPs) for Proteins: Computational and Experimental Studies of Acrylamide Based Polymers for Myoglobin

Abstract: Molecularly imprinted polymers (MIPs) have potential as alternatives to antibodies in the diagnosis and treatment of disease. However, atomistic level knowledge of the prepolymerization process is limited that would facilitate rational design of more efficient MIPs. Accordingly, we have investigated using computation and experiment the proteinmonomer binding interactions that may influence the desired specificity. Myoglobin was used as the target protein and five different acrylamide-based monomers considered.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
49
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 64 publications
(54 citation statements)
references
References 54 publications
4
49
0
1
Order By: Relevance
“…We produced a series of acrylamide-based (AAm, NHMAm, NHEAm, DMAm, and TrisNHMAm) hydrogel MIPs with selective recognition for the target protein myoglobin [ 30 ]. By comparing the MIPs with their corresponding non-imprinted polymer (NIP) controls, an imprinting factor (IF) was calculated, using equation ( 1 ) and used to assess performance.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We produced a series of acrylamide-based (AAm, NHMAm, NHEAm, DMAm, and TrisNHMAm) hydrogel MIPs with selective recognition for the target protein myoglobin [ 30 ]. By comparing the MIPs with their corresponding non-imprinted polymer (NIP) controls, an imprinting factor (IF) was calculated, using equation ( 1 ) and used to assess performance.…”
Section: Resultsmentioning
confidence: 99%
“…Monomers interacting with proteins could disrupt the secondary structure within the protein, especially if the monomer interactions are with functional groups along the protein backbone [ 50 ]. Indeed, Sullivan et al [ 30 ] showed that the hydroxyl groups in TrisNHMAm were able to strongly hydrogen bond to helical backbone residues within the potential binding sites of myoglobin leading to changes in this target’s secondary structure. In addition to this, TrisNHMAm has a low IF value of 1.10 suggesting that the MIP behaves similarly to the NIP and is therefore deemed unacceptable for use as a MIP.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Removal of the template molecule from the polymer results in the formation of specific binding cavities, complementary in terms of structure and functionality to the template molecule. [ 13–15 ] For several years MIPs were limited by high levels of heterogeneity and by synthetic methods, but significant advances in molecular modeling and understanding of polymer chemistry have countered these issues.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, there are several factors that significantly influence the generation of specific binding sites. A study by Sullivan et al demonstrated that acrylamide-based monomers that were smaller in size and that formed comparatively less hydrogen bonds with the side chains than the protein backbone, resulted in less secondary structural changes within the protein template prior to polymerisation [91]. Notably, if the conformational structure of the template protein is disturbed before or during polymerisation, the PIP will consist of binding sites that will inhibit rebinding.…”
Section: Protein Detectionmentioning
confidence: 99%